2022
DOI: 10.3390/su142215125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sound Source Landscape in Urban Forest Park on Alleviating Mental Stress of Visitors: Evidence from Huolu Mountain Forest Park, Guangzhou

Abstract: Urban Forest parks are indispensable areas in cities and have ecological and social advantages, and the quality of their acoustic landscapes is an important factor influencing visitors’ visiting experience. The purpose of this study was to investigate the factors influencing the acoustic landscape on psychological stress relief in selected urban forest parks in China. This study used a questionnaire to construct an index system for psychological stress reduction and designed a questionnaire for the perceived i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The W1 subsystem mainly reflects the utilization of WR (W1-1) and WR conditions (W1-2); the W2 subsystem mainly describes the environmental pressure of WR (W2-1) and the management level of environmental pollution and prevention (W2-2); the W3 subsystem mainly reflects the water ecological safety W3-1 and biodiversity W3-2; the W4 subsystem mainly reflects the economic dynamics of WR W4-1, economic strength W4-2 and economic scale W4-3. This study draws on the studies of Guo Yanlong et al [18,19] and De O. et al [20] on WRS, combined with the WR Evaluation Guide (SL/T238-1999), using data from 12 provincial administrative regions in western China for 2012-2022. By integrating relevant documentary standards and literature, this study combined entropy weight method and cloud model to construct a comprehensive evaluation model.…”
Section: Evaluation Indicator Construction and Data Calculationmentioning
confidence: 99%
“…The W1 subsystem mainly reflects the utilization of WR (W1-1) and WR conditions (W1-2); the W2 subsystem mainly describes the environmental pressure of WR (W2-1) and the management level of environmental pollution and prevention (W2-2); the W3 subsystem mainly reflects the water ecological safety W3-1 and biodiversity W3-2; the W4 subsystem mainly reflects the economic dynamics of WR W4-1, economic strength W4-2 and economic scale W4-3. This study draws on the studies of Guo Yanlong et al [18,19] and De O. et al [20] on WRS, combined with the WR Evaluation Guide (SL/T238-1999), using data from 12 provincial administrative regions in western China for 2012-2022. By integrating relevant documentary standards and literature, this study combined entropy weight method and cloud model to construct a comprehensive evaluation model.…”
Section: Evaluation Indicator Construction and Data Calculationmentioning
confidence: 99%
“…Walking, running, and other sports are better choices for restoration than just sitting or looking [ 21 ]. The recovery of stress is also related to multiple sensory modalities such as olfaction [ 22 ], audition [ 23 ], and tactile sensation [ 24 ], but the specific impact of visual stimuli remains relatively unclear, particularly regarding the diverse visual forms presented by green spaces and their restorative effects. Further research is needed to investigate this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of research area, most of the soundscape restorative research now is in public spaces such as urban parks, forest parks, college campuses, etc., and there are fewer researches involving rural tourist destinations. In addition, scholars have already confirmed that soundscape has restorative functions [72][73][74], but there is a lack of research on its influence mechanism with environmental restorative effects. Therefore, in this study, the Taohuayuan Scenic Area in Changde City, Hunan Province was selected as a case study for empirical analysis, with the main purpose of exploring the influence mechanism of Rural Soundscape Perception on Environmental Restoration Perception by constructing a structural equation model, and introducing the two affective variables of tourism nostalgia and place attachment, to provide new research perspectives for the theoretical study of Rural Soundscape Perception, and at the same time, to provide theoretical basis for the design and creation of soundscape in rural tourism destinations and decision-making support.…”
Section: Introductionmentioning
confidence: 99%